Neratinib enhances the efficacy of CDK4/6 inhibitor plus endocrine therapy in HR+/HER2-low breast cancer cell line ZR-75-1 via hsa-miR-23a-5p - Liushan Chen; Lingling Ye; Yuqi Liang; Wei Luo; Qian Zuo; Ping Huang; Yuyu Hu; Yan Dai; Yingchao Wu; Qianqian Guo; Qianjun Chen (Scientific Reports)
Abstract HR+/HER2-low breast cancer is a significant subgroup of conventional HR+/HER2-negative breast cancer, and combination of CDK4/6 inhibitor and endocrine therapy is the standard first-line and second-line treatments for advanced HR+/HER2-low breast cancer. Nevertheless, it remains uncertain whether HER2 signaling affects the effectiveness of CDK4/6 inhibitor administered in combination with endocrine therapy for HR+/HER2-low breast cancer and suitable intervention measures. This study revealed poor efficacy for CDK4/6 inhibitor combined with endocrine therapy for HR+/HER2-low breast cancer in vitro and in vivo models. Secondly, suppression of HER2 gene expression in HR+/HER2-low breast cancer cells resulted in significantly improved efficacy for CDK4/6 inhibitor combined with endocrine therapy. Furthermore, the anti-HER inhibitor neratinib was administered to enhance the effectiveness of CDK4/6 inhibitor combined with endocrine therapy in HR+/HER2-low breast cancer by inhibiting the HER2 pathway and lowering HER2 mRNA expression. Strikingly, neratinib reversed the efficacy of CDK4/6 inhibitor and endocrine therapy by reducing HER2 mRNA stability in HR+/HER2-low breast cancer through the interaction of HER2 3’-UTR region with hsa-miR-23a-5p. Even after reducing neratinib dosage to the standard 1/2 dose (20 mg/kg), it remained highly effective and well-tolerated. This study provides a viable and well-tolerated triple combination therapy for clinical HR+/HER2-low breast cancer.